2020
DOI: 10.3390/ijerph17207472
|View full text |Cite
|
Sign up to set email alerts
|

Betel-Quid Chewing, Heart Failure, and Premature Ventricular Contractions in Patients with Cardiopulmonary Symptoms

Abstract: Betel-quid (BQ) is a commonly used psychoactive substance that renders a specific cardiotoxicity. The purpose of this study was to investigate the association between BQ chewing and premature ventricular contractions (PVC) in patients with cardiopulmonary symptoms, and examine the potential influences of cardiovascular and chronic diseases on such relationship. Participants were 146 patients with cardiopulmonary symptoms who participated in 24-h Holter electrocardiogram monitoring during 2012–2018 in a hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The consumption and medicinal use of Arecae Semen exhibit distinct levels of toxicity. Studies have demonstrated that the habitual chewing of edible Arecae Semen increases the risk of heart failure, ventricular premature beats, and oral cancer [ 32 , 70 ]. In contrast, the use of Arecae Semen in TCM often involves its combination with other herbal ingredients, as seen in Simo Mixture, where Arecae Semen is mixed with Muxiang, Zhike, Wuyao, and others, undergoing specific processing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption and medicinal use of Arecae Semen exhibit distinct levels of toxicity. Studies have demonstrated that the habitual chewing of edible Arecae Semen increases the risk of heart failure, ventricular premature beats, and oral cancer [ 32 , 70 ]. In contrast, the use of Arecae Semen in TCM often involves its combination with other herbal ingredients, as seen in Simo Mixture, where Arecae Semen is mixed with Muxiang, Zhike, Wuyao, and others, undergoing specific processing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Arecoline causes neurotoxicity through enhancement of oxidative stress and suppression of the antioxidant protective system [ 43 ]. Several studies have been reported that betel nut chewing induced cardiac dysrhythmias [ 28 , 44 ]. However, the molecular mechanisms in which arecoline-induced cardiac dysfunction is needed to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior of chewing areca nuts habitually has been found to cause cardiotoxicity, including coronary artery disease [ 27 ], heart failure, and premature ventricular contractions [ 28 ]. However, there is a lack of research investigating the effect of arecoline on cardiac fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies were done in Taiwan (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), three studies done in Pakistan (29)(30)(31) and three studies in Bangladesh (32)(33)(34). There were nine crosssectional studies (16)(17)(18)20,(24)(25)(26)(27)31), seven prospective cohort studies (19,22,28,29,(32)(33)(34), two casecontrol studies (23,30) and one experimental design (21). Of the nine cross-sectional studies, eight were done in Taiwan (16)(17)(18)20,(24)(25)(26)(27) and one in Pakistan (31).…”
Section: Study Setting and Study Designmentioning
confidence: 99%
“…Betel quid use is a risk factor for arrhythmias (24) and premature ventricular contractions (PVCs) (18). In a nationwide ecological study, Tsai et al (2013) found a positive correlation (r=0.558, p=0.07) between areca quid chewing and atrial fibrillation (AF).…”
Section: Arrhythmiamentioning
confidence: 99%